PENGARUH PENERAPAN E-LEARNING TERHADAP PRESTASI BELAJAR MAHASISWA (STUDI KASUS PADA MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA) - Reni Suendari; Suparno Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The aim of this study is to examine the effect of using e-learning tools on students achievement in learning who are majoring in accounting at Faculty of Economics and Business, Syiah Kuala University. This research uses quantitave research approach with the type of case study. The data used in this study is primary data by distributing questionnaires directly to all respondents. The population in this study is all students who are majoring in accounting at Faculty of Economics and Business, Syiah Kuala University. The sampling technique used in this study is Judment sampling. The number of questionnaires that have been analyzed are 33 questionnaires. Testing the effect of independent variable on the dependent variable was done by using simple linear regression model with SPSS. The result of this study indicates that the use of e-learning has a positive effect on students achievement in learning who are majoring in accounting at the Faculty of Economics and Business, Syiah Kuala University.